2013
DOI: 10.1111/irv.12210
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the performance of a rapid antigen test for the detection of influenza virus in clinical specimens from children in Cameroon

Abstract: The performance of SD Bioline rapid antigen test (RAT) was evaluated using real-time reverse transcription polymerase chain reaction (rRT-PCR) as gold standard. A total of 718 nasal swabs, including 102 rRT-PCR positive and 616 rRT-PCR negative swabs, were tested. RAT demonstrates a sensitivity of 29·4% with a specificity of 100%. The positivity rate of RAT was highly associated with lower cycle threshold (Ct) values (P < 0·0001). The excellent specificity of the RAT allowed for the rapid identification of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
2
4
1
Order By: Relevance
“…These results are different from those found in the Centre region of Cameroon by Heraud et al. (2008‐2009), 16 Kenmoe et al, and Monamele et al who found that influenza circulated throughout the year or with a seasonal peak (May through November) . On the other hand, our results corroborate with reports of Caini et al who observed a heterogeneous pattern in the circulation of influenza virus across several tropical countries since none of the peaks observed in this study were overlapping.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…These results are different from those found in the Centre region of Cameroon by Heraud et al. (2008‐2009), 16 Kenmoe et al, and Monamele et al who found that influenza circulated throughout the year or with a seasonal peak (May through November) . On the other hand, our results corroborate with reports of Caini et al who observed a heterogeneous pattern in the circulation of influenza virus across several tropical countries since none of the peaks observed in this study were overlapping.…”
Section: Discussioncontrasting
confidence: 81%
“…The first results showed the circulation of A/ H1N1/2009, A/H3N2, and B viruses 12 with a high circulation in the rainy season. 13,14 A recent study performed in Yaounde found no significant association between influenza activity and three meteorological variables (temperature, rainfall, and RH) though some synchronies were observed with rainfall. 15 The town of Garoua is located in northern Cameroon and is dominated by a Sudan tropical climate, with high temperatures that can exceed 30°C.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies have evaluated the use of rapid influenza diagnostic tests compared to rRTPCR. Kenmoe et al in Cameroon found a lower sensitivity (29.4%) of the SD Bioline rapid antigen test 210 while Ndegwa et al in Kenya found acceptable sensitivity (77.1%) for the Becton Dickinson Veritor™ System Flu A + B rapid influenza diagnostic test (RIDT) 211 . Both studies concluded the advantage of using a rapid test for identification of influenza cases with regard to the high specificity (100%) although recommending that negative results be confirmed by rRT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 5 articles have evaluated diagnostic techniques for influenza detection 157,[208][209][210][211] . Two studies from Tunisia and South Africa evaluated the use of multiplex rRT-PCR in the identification of respiratory viruses with a sensitivity > 90% and Specificity of 100% thus allowing effective and fast diagnosis of respiratory viral infections 157,208 .…”
Section: Influenza Diagnosticmentioning
confidence: 99%